The Work of Veronica Strong-Boag - Forestell, Nancy; McPherson, Kathryn; Campbell, Lara; Llewellyn, Kristina (Atlantis)

(untitled) (Mount Saint Vincent University, 2013)
The pieces in this cluster originated roundtable, “Veronica Strong-Boag, Canadian Feminist Historian: An Assessment and Appreciation” at the 2010 Canadian Committee on Women’s History conference held in Vancouver. A multiple award-winning feminist scholar who has published numerous books, edited collections, and journal articles, Veronica Strong-Boag has had an enormous influence on Canadian history in general and Canadian women’s and gender history in particular. Throughout an academic career which has now spanned almost four decades, Strong-Boag has taught undergraduates and supervised graduate students in history, women’s and gender studies, and education-al studies. Her impressive body of research includes historical studies of feminism, female pacifists, women in suburbia, E. Pauline Johnson, child welfare, adoption, and fostering. As the pieces in this cluster well illustrate, Strong-Boag is admired and respected by her feminist colleagues as an esteemed academic, supportive mentor, and committed feminist.